MANAJEMEN KEMANDIRIAN PESANTREN BERBASIS KOPERASI DI PONDOK PESANTREN SIDOGIRI - Mokh. Syaiful Bakhri; Ashari Ashari (Pusat Riset dan Inovasi Nasional, 2023)
The Ministry of Religion of the Republic of Indonesia assesses that there are still many Islamic boarding schools that have not yet been established, so they need to strive for their independence. For this reason, the Ministry of Religion has launched the “Pesantren Independence Road Map” (2021). This study examines the independence of Islamic boarding schools based on kopontren at the Sidogiri Islamic Boarding School (PPS). The aim is to prove the independence of PPS. The research method used is qualitative research which analyzes data in the form of statements and documentation. From the research conducted, it was found evidence that PPS is an independent Islamic boarding school both in terms of institutional, management, curriculum, manpower and funding aspects. This independence is achieved through the implementation of management principles such as planning, organizing, acting and controlling in managing the pesantren. In addition, the study also found that there are seven characteristics of PPS independence, namely having a business charity that is able to finance the financial needs of the pesantren, being able to manage its finances from the time the students register to completing their studies at the pesantren, being able to meet the basic needs of the students, being able to manage and determine the educational curriculum for the students. santri independently, not asking for help from other parties or the government to build pesantren. In addition, it has educational institutions, da'wah, social, economic and alumni networks that support the independence of pesantren.